Gallbladder cancer: current and future treatment options - Zhou, Yanzhao; Yuan, Kun; Yang, Yi; Ji, Zemin; Zhou, Dezheng; Ouyang, Jingzhong; Wang, Zhengzheng; Wang, Fuqiang; Liu, Chang; Li, Qingjun; Zhang, Qi; Li, Qiang; et al. (Frontiers in Pharmacology, 2023)
Surgery remains the preferred treatment option for early-stage gallbladder cancer (GBC). According to the anatomical position of the primary tumor, accurate preoperative stage and strict control of surgical indications, appropriate surgical strategies are selected to achieve the optimal surgical effect. However, most patients have already been at the locally advanced stage or the tumor has metastasized at the initial diagnosis. The postoperative recurrence rate and 5-year survival rate remain unsatisfactory even after radical resection for gallbladder cancer. Hence, there is an urgent need for more treatment options, such as neoadjuvant therapy, postoperative adjuvant therapy and first-line and second-line treatments of local progression and metastasis, in the whole-course treatment management of gallbladder cancer patients. In recent years, the application of molecular targeted drugs and immunotherapy has brought greater hope and broader prospects for the treatment of gallbladder cancer, but their effects in improving the prognosis of patients still lack sufficient evidence-based medicine evidence, so many problems should be addressed by further research. Based on the latest progress in gallbladder cancer research, this review systematically analyzes the treatment trends of gallbladder cancer.